Mitochondrial inhibitor atovaquone increases tumor oxygenation and inhibits hypoxic gene expression in patients with non-small cell lung cancer - Skwarski, M; McGowan, D; Belcher, E; Di Chiara, F; Stavroulias, D; McCole, M; Derham, J; Chu, K-Y; Teoh, E; Chauhan, J; O'reilly, D; Harris, B; et al. (American Association for Cancer Research, 2021)
Purpose: Tumor hypoxia fuels an aggressive tumor phenotype and confers resistance to anticancer treatments. We conducted a clinical trial to determine whether the antimalarial drug atovaquone, a known mitochondrial inhibitor, reduces hypoxia in non-small cell lung cancer (NSCLC). Patients and methods: Patients with NSCLC scheduled for surgery were recruited sequentially into two cohorts: Cohort 1 received oral atovaquone at the standard clinical dose 750 mg twice-daily whilst Cohort 2 did not. Primary imaging endpoint was change in tumor hypoxic volume (HV) measured by hypoxia PET-CT. Inter-cohort comparison of hypoxia gene expression signatures using RNAseq from resected tumors was performed. Results: Thirty patients were evaluable for hypoxia PET-CT analysis, 15 per cohort. Median treatment duration was 12 days. Eleven (73.3%) atovaquone-treated patients had meaningful HV reduction with median change -28.0% (95% CI, -58.2 to -4.4). In contrast, median change in untreated patients was +15.5% (95% CI, -6.5 to 35.5). Linear regression estimated the expected mean HV was 55% (95% CI, 24% to 74%) lower in Cohort 1 compared to Cohort 2 (p=0.004), adjusting for cohort, tumor volume and baseline HV. A key pharmacodynamic endpoint was reduction in hypoxia regulated genes, which were significantly downregulated in atovaquone-treated tumors. Data from multiple additional measures of tumor hypoxia and perfusion are presented. No atovaquone-related adverse events were reported. Conclusions: This is the first clinical evidence that targeting tumor mitochondrial metabolism can reduce hypoxia and produce relevant anti-tumor effects at the mRNA level. Repurposing atovaquone for this purpose may improve treatment outcomes for NSCLC.